Perception on Mandarin Oral Presentation Among Non-Chinese Students - Yong, Ying Mei; Sharifah Intan Safina, Syed Zubir (2015)
Learning Mandarin as a foreign language is gaining its popularity among non-Chinese students in the institutions of higher learning in Malaysia. It is observed that the language performance is different among students in Mandarin speaking, especially non-Chinese students learning Mandarin as a foreign language. Some students demonstrate good performance in Mandarin oral presentations while some students are weak. The objective of the study is to determine the perception of non-Chinese students towards Mandarin oral presentations. Due to the knowledge that public speaking is an important social skill(Spitzberg and Cupach, 1989) and the fear of it has been described as the most common fear among students (Geer, 1965), the study is attempted. A total of 195 non-Chinese students who have enrolled in the Mandarin for Beginners Course took part as the respondents of the study. A set of questionnaire was used to acquire the respondents’ background and to gain an insight on the perception of the respondents. The finding is presented in descriptive statistics where the preparation for oral presentations, oral presentations itself and the expectations from oral presentations are presented. The article concludes with the suggestions to enhance Mandarin oral presentation strategies among non-Chinese students.